PENGARUH KINERJA SOSIAL PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - , Yusuf Indrajaya; , Dr. Mamduh M. Hanafi, MBA, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims at examining the effect of corporate social responsibility on corporate financial performance moderated by firm size. The sample was non financial companies that has been listed on Indonesian Stock Exchange (IDX) period 2007-2010 with one-year time lag